PENGARUH PERTUMBUHAN PERUSAHAAN, PROFITABILITAS, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Filbert, Jonnardi (Jurnal Paradigma Akuntansi, 2020)
The purpose of this empirical research is to examine the influence of firm growth, profitability, and capital structure toward firm value. This research uses 38 samples real estatecompany listed on the Indonesia Stock Exchange in the year of 2014-2018. Data processing techniques in this research using program Eviews version 10.0. The results of this research indicate that independent variables firm growth and capital structure have a significant effect on firm value but profitability does not have a significant effect on firm value.